Hyperbilirubinemia after surgical repair for acute type a aortic dissection: A propensity score-matched analysis - Wang, Zhigang; Xu, Jingfang; Cheng, Xiaofeng; Zhang, Lifang; Wang, Dongjin; Pan, Jun (Frontiers in Physiology, 2022)
Background: Inflammation and oxidative stress are known to participate in the pathogenesis of hyperbilirubinemia. It has been known that acute type A aortic dissection (ATAAD) surgical repair often associates with complications which might affect the long-term prognosis. However, the clinical significance of postoperative hyperbilirubinemia (PH) has not been evaluated. Here in this study, we examined the incidence, risk factors, and prognosis of PH after ATAAD surgery. Methods: This retrospective study enrolled a total of 970 patients who received ATAAD surgical repair from January 2014 to December 2019. PH was defined as serum total bilirubin > 3.0 mg/dl within the first week after the surgery. Propensity score matching was used to reduce selection bias and eliminate potential confounding factors. Kaplan- Meier survival and Cox proportional hazards regression analyses were conducted to explore the association between PH and postoperative long-term survival. Results: Development of PH (183 patients) was associated with a higher 30-Day mortality (20.8% vs. 9.0%, P < 0.001). Advanced age [odds ratio (OR) 1.538, P = 0.006], higher baseline total bilirubin level (OR 1.735, P = 0.026), preoperative pericardial tamponade (OR 3.192, P = 0.024), prolonged cardiopulmonary bypass (CPB) duration (OR 2.008, P = 0.005), and elevated postoperative central venous pressure (CVP) level (OR 2.183, P < 0.001) were associated with PH. The Kaplan-Meier analysis showed patients who developed PH were associated with poor long-term survival (P = 0.044). Cox analysis showed that the presence of PH (hazard ratio 2.006, P = 0.003) was an independent risk factor for increased mortality. Conclusions: PH is a common complication in patients undergoing ATAAD surgical repair that associates with worse short- and long-term prognosis. Our data indicated that age, preoperative total bilirubin level, pericardial tamponade, CPB duration, and postoperative CVP level were risk factors for the development of PH.